Formulasi Sediaan Krim Tabir Surya Ekstrak Etanolik Daun Leunca (Solanum Nigrum L.) Dan Uji Sun Protection Factor (SPF) - Vicko Suswidiantoro; Dila Cindy Reptiana; Haikal Nur Islam; Hazballah Asy Syifa; Miftah Khoirun Nissa; Audya Zahra; Eva Nurul Baity; Wulan Cahya Indah; Wina Safutri; Riza Dwiningrum; Mida Pratiwi; Iga Mayola Pisacha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Human skin is a very important organ because it is located on the outside of the body and functions to receive external stimuli such as touch, pain, and other influences. One cause of damage is ultraviolet (UV) rays. Leunca leaves (Solanum nigrum L.) have high antioxidant activity, which is associated with their flavonoid content, especially quercetin and kaempferol. The purpose of this study was to determine the characteristics of sunscreen cream preparations from ethanolic extract of leunca leaves (Solanum nigrum L.) and to determine the concentration of ethanolic extract of leunca leaves (Solanum nigrum L.) in cream preparations that provide good sunscreen potential based on the Sun Protection Factor (SPF) value. The method used was experimental in making sunscreen cream preparations with concentrations F1 (0.05%), F2 (0.10%), F3 (0.20%) and F4 (0.30%). Physical quality tests, organoleptic tests, homogeneity tests, Ph tests, spreadability tests, and adhesion tests were carried out. protection power test, viscosity test, cream type test and SPF value test. In the four formulations meet the physical quality test requirements that distinguish them are in the Sun Protection Factor (SPF) value. The best is in formulation 4, which is 2.19, which is included in the minimum protection